2022
DOI: 10.1002/ajpa.24609
|View full text |Cite
|
Sign up to set email alerts
|

Missing data in bioarchaeology I: A review of the literature

Abstract: Objectives: Missing data are a frequent and unavoidable challenge in bioarchaeological research, yet researchers seldom make explicit statements about the bias and inferential limitations that missing data introduce into their studies. There are no guidelines for best practices for the treatment or reporting of missing data. As an initial step in taking stock and exploring approaches to missing data in bioarchaeology, this study reviews bioarchaeological publications to identify methods currently in use for ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Missing data are a common problem in forensic and archeological anthropology (Kenyhercz et al, 2019; Wissler et al, 2022a). In both fields, researchers often encounter bones and artifacts that are incomplete or fragmented.…”
Section: Introductionmentioning
confidence: 99%
“…Missing data are a common problem in forensic and archeological anthropology (Kenyhercz et al, 2019; Wissler et al, 2022a). In both fields, researchers often encounter bones and artifacts that are incomplete or fragmented.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, archaeo-historical data can suffer from the problem of forward bias (Beheim et al 2021), as the first observed instance of evidence is unlikely to be the true first occurrence, with the true first occurrence happening potentially hundreds or thousands of years prior. In bioarchaeology there is little consideration given to how missing data may bias findings, and the majority of studies do not have a stated approach for handling missing data (Wissler, Blevins, and Buikstra 2022).…”
Section: Introductionmentioning
confidence: 99%